Regenerative therapies for tympanic membrane. (June 2022) - Anand, Shivesh; Danti, Serena; Moroni, Lorenzo; Mota, Carlos
Abstract: It is estimated that by 2050 one in every ten people will be suffering from disabling hearing loss. Perforated tympanic membranes (TMs) are the most common injury to the human ear, resulting in a partial or complete hearing loss due to inept sound conduction. Commonly known as the eardrum, the TM is a thin, concave tissue of the middle ear that captures sound pressure waves from the environment and transmits them as mechanical vibrations to the inner ear. Microsurgical placement of autologous tissue graft has been the "gold standard" for treating damaged TMs; however, the incongruent structural and mechanical properties of these autografts often impair an optimal hearing restoration following recovery. Moreover, given the lack of available tissues for transplantations, regenerative medicine has emerged as a promising alternative. Several tissue engineered approaches applying bio-instructive scaffolds and stimuli have been reported for the TM regeneration, which can be broadly classified into TM repair and TM reconstruction. This review evaluates the current advantages and challenges of both strategies with a special focus on the use of recent biofabrication technologies for advancing TM tissue engineering.